GURU PENDIDIKAN AGAMA KRISTEN, KUALITAS PENDIDIKAN DAN MASA DEPAN MORALITAS BANGSA DUNIA - Desire Karo Karo; Urbanus Sukri; Simeon Sulistyo; Indro Puspito; Theresia Christina (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2018)
This paper aims to provide an understanding that Christian Education teachers have a significant role in improving the quality of education and the future of national morality. The development of globalization and modernization makes teachers must be ready and contribute in preparing the nation's young generation in entering the era of globalization and modernization. At least there are two roles that must be possessed by the Christian Religious Education teacher, namely participating in realizing quality education and maintaining the nation's morality. With this writing, it is expected that every Christian Education teacher will become more aware and more enthusiastic in carrying out his duties and vocation as a teacher of Christian Religious Education.